STRATEGIC DIRECTIONS OF DEVELOPMENT OF FINANCIAL ARCHITECTURE OF THE ECONOMY OF UKRAINE - Zhytar, Maksym; Samorodov, Borys; Sosnovska, Olga (FINANCIAL AND CREDIT SYSTEMS: PROSPECTS FOR DEVELOPMENT, 2021)
The article considers the strategic directions of development of the financial architecture of the Ukrainian economy. It is proved that it is necessary to pay close attention to the following areas: the use of specific accounting standards; promoting the increase of the level of transparency of domestic capital markets in the context of introduction of complex market segments and financial instruments for coordinated regulation, first of all, including relevant derivatives; organization of effective prudential regulation and control over banking institutions; systemic risk management of the banking sector; increasing the effectiveness of control over institutions that are insured in a single system of insurance of their deposits; consolidation of supervision in the context of the use of a wider range of diversified instruments in order to control and limit the relevant financial risks that are directly related to the activities of a particular consolidated group; development of special programs to control companies with a complex structure, on the basis of using a system of indicators to identify possible problems and imbalances, corporate risks that arise directly, the formation of a strict regime of control over all functionally strategic financial organizations.